Antioxidant activity and characterization of arrowroot (Maranta arundinacea) tuber yogurt - SITARESMI YUNINGTYAS; ANNA PRIANGANI ROSWIEM; DINA AZAHRA; MUHAMMAD ALFARABI (Society for Indonesian Biodiversity, 2023)
Abstract. Yuningtyas S, Roswiem AP, Azahra D, Alfarabi M. 2023. Antioxidant activity and characterization of arrowroot (Maranta arundinacea) tuber yogurt. Biodiversitas 24: 2850-2854. The main benefit of yogurt is its ability to improve the digestive health tract by enhancing the condition of the intestinal flora and its environment. Nowadays, adding natural ingredients to yogurt is a widely practiced trend towards further increasing its efficacy as a healthy drink. Arrowroot tuber (Maranta arundinacea L.) is a food source with many health benefits and is not yet widely used in Indonesia. Fermentation can increase the health value of a food product compared to existing products. Therefore, the novelty and objective of this study are to produce and characterize arrowroot tuber yogurt using two species of Lactic Acid Bacteria (LAB), Lacticaseibacillus casei and Lactiplantibacillus plantarum. These LAB species are used for yogurt starter and arrowroot tuber as a substrate in the fermentation process. The fermentation process was carried out using a combination of L. plantarum and L. casei (1:1 % (v / v)), L. plantarum 2% (v / v), and L. casei 2% (v / v). The characterization involved determining the pH value, total lactic acid level, total lactic acid bacteria level, and the antioxidant activity of the yogurt, which was assessed using the free radical 2,2-Diphenyl-1-Picrilhydrazyl (DPPH). The result showed that all arrowroot tuber yogurts have antioxidant activity, with the ability to inhibit DPPH by 59.30-86.62%. The arrowroot tuber yogurt had a pH level of 4.29-4.81, total lactic acid of 0.87-0.95%, and total lactic acid bacteria of 7.5×107-7.6×109 CFU/mL, all of which complied with the characteristics of the probiotic drink standard set by the Indonesian National Standard 2981:2009. These findings suggest that arrowroot tuber yogurt has the potential to be developed into a healthy drink.